Penambahan Gedebong Pisang pada Kompos Bulu Ayam dengan Berbagai Jenis Aktivator - Kusmiadi, Riwan; Khodijah, Nyayu Siti; Royalaitani, . (Universitas Bangka Belitung, 2015)
Agricultural activities always produce solid waste which originated from residues of livestock and crop. Chicken feathers and banana trunk are waste that have potential to be utilized as compost material. It is due to chicken feathers contains high protein so that it can be used as a source of nitrogen. Meanwhile, banana trunk contains high potassium. Decomposition of compost material needs a lot of time. However, composting can be conducted faster by using microorganisms. The purpose of this study is to determine the effect of banana trunk and the effectivity of local microorganism in the decomposition of compost material. This study uses randomized block design factorial with six treatments. First factor is banana trunk (0.5 and 1 kg). The second factor is activator types (EM4, MOL tapai and MOL papaya).The variables were temperature, water content, color, pH, N-total, C-organic, ratio C/N, phospor, and potassium. The result showed that banana trunk was statistically significant to water content, ratio C/N and potassium. Furthermore, the activators did not affect physical and chemical properties of compost.Â